Identification of a mammalian nuclear factor and human cDNA-encoded proteins that recognize DNA containing apurinic sites. - Lenz, J (1990)
Damage to DNA can have lethal or mutagenic consequences for cells unless it is detected and repaired by cellular proteins. Repair depends on the ability of cellular factors to distinguish the damaged sites. Electrophoretic binding assays were used to identify a factor from the nuclei of mammalian cells that bound to DNA containing apurinic sites. A binding assay based on the use of beta-galactosidase fusion proteins was subsequently used to isolate recombinant clones of human cDNAs that encoded apurinic DNA-binding proteins. Two distinct human cDNAs were identified that encoded proteins that bound apurinic DNA preferentially over undamaged, methylated, or UV-irradiated DNA. These approaches may offer a general method for the detection of proteins that recognize various types of DNA damage and for the cloning of genes encoding such proteins.